Halogenated Phenazines that Potently Eradicate Biofilms, MRSA Persister Cells in Non‐Biofilm Cultures, and Mycobacterium tuberculosis. (20th October 2015) - Garrison, Aaron T.; Abouelhassan, Yasmeen; Kallifidas, Dimitris; Bai, Fang; Ukhanova, Maria; Mai, Volker; Jin, Shouguang; Luesch, Hendrik; Huigens, Robert W.
Abstract: Conventional antibiotics are ineffective against non‐replicating bacteria (for example, bacteria within biofilms). We report a series of halogenated phenazines (HP), inspired by marine antibiotic 1, that targets persistent bacteria. HP 14 demonstrated the most potent biofilm eradication activities to date against MRSA, MRSE, and VRE biofilms (MBEC=0.2–12.5 μM), as well as the effective killing of MRSA persister cells in non‐biofilm cultures. Frontline MRSA treatments, vancomycin and daptomycin, were unable to eradicate MRSA biofilms or non‐biofilm persisters alongside 14 . HP 13 displayed potent antibacterial activity against slow‐growing M.   tuberculosis (MIC=3.13 μM), the leading cause of death by bacterial infection around the world. HP analogues effectively target persistent bacteria through a mechanism that is non‐toxic to mammalian cells and could have a significant impact on treatments for chronic bacterial infections. Abstract : Kampf den ruhenden Bakterien ! Biofilme und persistierende Zellen sind üblicherweise resistent gegen Standard‐Antibiotika und tragen somit zu vielen Infektionen bei. Halogenierte Phenazine auf der Basis mariner Naturstoffe bekämpfen Biofilme und derartige Zellen wirksam, bei geringer Zytotoxizität gegen Säugerzellen.